Sustainability - Larsson, Daniel (2008)
This master thesis aims to examine the theory of sustainability. A concept that has become an integrated part of our lives and for the landscape architect and architect an ever more important factor to consider. But what does sustainability or sustainable development mean, where does the theory come from and who came up with the ideas? And how is this elusive and complex theory to be implemented on site? This thesis is divided into three parts. The first part will examine the theoretical aspect of the subject through contemporary, as well as historic perspectives. The second part aims to take the discussion down to site where the implementation of one sustainability theory is tested. The last part will draw upon the conclusions made and formulate visions regarding a sustainable future.